Stability and dynamics of membrane-spanning DNA nanopores - Vishal Maingi (Nature Portfolio, 2017)
Although DNA nanopores are widely explored as synthetic membrane proteins, it is still unclear how the anionic DNA assemblies stably reside within the hydrophobic core of a lipid bilayer. Here, the authors use molecular dynamics simulations to reveal the key dynamic interactions and energetics stabilizing the nanopore-membrane interaction.